EKSPLORASI GOWE NILARE SEBAGAI MEDIA PEMBELAJARAN BERBASIS BUDAYA PADA MATERI LINGKARAN - Laowo, Nasowaauri; Hardi Tambunan; Ruth Mayasari Simanjuntak (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study aims to explore the use of Gowe Nilare, a traditional Nias game, as a culturally based learning medium in teaching the concept of circles. The research employed a literature review approach, collecting and analyzing sources related to local culture, mathematical concepts of circles, and experiential learning theory. The findings indicate that Gowe Nilare physically and structurally represents the concept of a circle, both in the formation of players and in the repetitive, cyclical rhythm of movements. The use of this medium not only reinforces students' understanding of circles in a concrete and contextual manner but also enhances engagement and motivation through an instructional approach that integrates local cultural values. Furthermore, Gowe Nilare serves as a tool to strengthen cultural identity and social values such as togetherness and collaboration in the learning process. Thus, Gowe Nilare can be considered an effective and relevant alternative learning medium, while also supporting the preservation of traditional culture within modern educational contexts. This study recommends the broader development and implementation of culturally based learning media to enrich teaching methods in schools.